PENGARUH KOORDINASI UNIT AERODROME CONTROL TOWER DENGAN UNIT APRON MOVEMENT CONTROL TERHADAP KELANCARAN PELAYANAN LALU LINTAS PENERBANGAN DI BANDAR UDARA SYAMSUDIN NOOR BANJARMASIN - Kartika Diah Setyowati; Laila Rochmawati; Yuni Saptandari (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This final project research entitled The Effect of Coordination of the Aerodrome Control Tower Unit with the Apron Movement Control Unit on the Smoothness of Aviation Traffic Services at Syamsudin Noor Airport Banjarmasin. The problem that is taken is how does the coordination between the Aerodrome Control Tower unit and the Apron Movement Control Unit affect the smooth flow of air traffic services at Syamsudin Noor Airport Banjarmasin?. Because there is a delay in providing parking stand information so it needs to be reviewed. This final project aims to determine the effect of coordination between the Aerodrome Control Tower (ADC) and Apron Movement Control (AMC) that occurred at Syamsudin Noor Airport, Banjarmasin. The research method that the author uses is quantitative. Data collection techniques in the form of observation, documentation in the form of logbooks and questionnaires.using observation, documentation, questionnaires. The results of this study indicate that there is an effect of coordination between the Aerodrome Control Tower unit and Apron Movement Control on air traffic services at Syamsudin Noor Airport Banjarmasin with a correlation coefficient of 0.825, which means that the relationship between these variables is strong. The coefficient of determination is 68%.